Mitochondrial Respiratory Inhibition Promoted by Pyraclostrobin in Fungi is Also Observed in Honey Bees - Nicodemo, Daniel [UNESP]; Mingatto, Fábio Erminio [UNESP]; De Jong, David; Bizerra, Paulo Francisco Veiga [UNESP]; Tavares, Marco Aurélio [UNESP]; Bellini, William Cesar [UNESP]; Vicente, Eduardo Festozo [UNESP]; de Carvalho, Amanda [UNESP] (Oxford University Press (OUP), 2020)
There is no use restriction associated with bees for many fungicides used in agriculture; however, this does not always mean that these pesticides are harmless for these nontarget organisms. We investigated whether the fungicide pyraclostrobin, which acts on fungal mitochondria, also negatively affects honey bee mitochondrial bioenergetics. Honey bees were collected from 5 hives and anesthetized at 4 °C. The thoraces were separated, and mitochondria were isolated by grinding, filtering, and differential centrifugation. An aliquot of 0.5 mg of mitochondrial proteins was added to 0.5 mL of a standard reaction medium with 4 mM succinate (complex II substrate) plus 50 nM rotenone (complex I inhibitor), and mitochondrial respiration was measured at 30 °C using a Clark-type oxygen electrode. Mitochondrial membrane potential was determined spectrofluorimetrically using safranin O as a probe, and adenosine triphosphate (ATP) synthesis was determined by chemiluminescence. Pyraclostrobin at 0 to 50 μM was tested on the mitochondrial preparations, with 3 repetitions. Pyraclostrobin inhibited mitochondrial respiration in a dose-dependent manner at concentrations of 10 μM and above, demonstrating typical inhibition of oxidative phosphorylation. Pyraclostrobin also promoted a decline in the mitochondrial membrane potential at doses of 5 μM and above and in ATP synthesis at 15 μM and above. We conclude that pyraclostrobin interferes with honey bee mitochondrial function, which is especially critical for the energy-demanding flight activity of foraging bees. Environ Toxicol Chem 2020;39:1267–1272. © 2020 SETAC.
Keywords: Adenosine triphosphate; Apis mellifera; Fungicide; Mitochondria; Strobilurin; Toxicity mechanism